High‐Performance Piezo‐Electrocatalytic Sensing of Ascorbic Acid with Nanostructured Wurtzite Zinc Oxide. Issue 51 (27th September 2021) - Liu, Nianzu; Wang, Ruoxing; Gao, Shengjie; Zhang, Ruifang; Fan, Fengru; Ma, Yihui; Luo, Xiliang; Ding, Dong; Wu, Wenzhuo
Abstract: Nanostructured piezoelectric semiconductors offer unprecedented opportunities for high‐performance sensing in numerous catalytic processes of biomedical, pharmaceutical, and agricultural interests, leveraging piezocatalysis that enhances the catalytic efficiency with the strain‐induced piezoelectric field. Here, a cost‐efficient, high‐performance piezo‐electrocatalytic sensor for detecting l ‐ascorbic acid (AA), a critical chemical for many organisms, metabolic processes, and medical treatments, is designed and demonstrated. Zinc oxide (ZnO) nanorods and nanosheets are prepared to characterize and compare their efficacy for the piezo‐electrocatalysis of AA. The electrocatalytic efficacy of AA is significantly boosted by the piezoelectric polarization induced in the nanostructured semiconducting ZnO catalysts. The charge transfer between the strained ZnO nanostructures and AA is elucidated to reveal the mechanism for the related piezo‐electrocatalytic process. The low‐temperature synthesis of high‐quality ZnO nanostructures allows low‐cost, scalable production, and integration directly into wearable electrocatalytic sensors whose performance can be boosted by otherwise wasted mechanical energy from the working environment, for example, human‐generated mechanical signals. Abstract : A cost‐efficient, high‐performance piezo‐electrocatalytic sensor is designed for detecting l ‐ascorbic acid (AA), a critical chemical for many organisms, metabolic processes, and medical treatments. The electrocatalytic efficacy of AA is significantly boosted by the piezoelectric polarization induced in nanostructured semiconducting zinc oxide catalysts.